2018
DOI: 10.1038/s41598-018-26274-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing of Patients from Multicase Families with Systemic Lupus Erythematosus Identifies Multiple Rare Variants

Abstract: In an effort to identify rare alleles associated with SLE, we have performed whole exome sequencing of the most distantly related affected individuals from two large Icelandic multicase SLE families followed by Ta targeted genotyping of additional relatives. We identified multiple rare likely pathogenic variants in nineteen genes co-segregating with the disease through multiple generations. Gene co-expression and protein-protein interaction analysis identified a network of highly connected genes comprising sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 95 publications
1
15
0
Order By: Relevance
“…Indeed, the team concluded that ATP depletion in combination with downregulation of ATP-dependent genes ERCC2 and ERCC5 suggest insufficient DNA repair in SLE patients, resulting in increased apoptosis and perpetuation of autoimmunity. Moreover, in order to identify rare alleles associated with SLE, Delgado-Vega and colleagues performed whole exome sequencing in SLE patients from well-studied Icelandic SLE multi-case families [122]. They found rare, possibly pathogenic variants in 19 genes, including the X-ray repair cross-complementation group 6 binding protein 1 (XRCC6BP1), also termed Ku70-binding protein 3 (KUB3).…”
Section: Increased Endogenous Dna Damage In Sle: Defective Repair or mentioning
confidence: 99%
“…Indeed, the team concluded that ATP depletion in combination with downregulation of ATP-dependent genes ERCC2 and ERCC5 suggest insufficient DNA repair in SLE patients, resulting in increased apoptosis and perpetuation of autoimmunity. Moreover, in order to identify rare alleles associated with SLE, Delgado-Vega and colleagues performed whole exome sequencing in SLE patients from well-studied Icelandic SLE multi-case families [122]. They found rare, possibly pathogenic variants in 19 genes, including the X-ray repair cross-complementation group 6 binding protein 1 (XRCC6BP1), also termed Ku70-binding protein 3 (KUB3).…”
Section: Increased Endogenous Dna Damage In Sle: Defective Repair or mentioning
confidence: 99%
“…We recently described the identification of many rare mutations in Icelandic families with multiple cases of SLE [14••]. By performing exome sequencing on the most distantly related affected individuals from two large families and verifying some of the mutations through genotyping or Sanger sequencing, we identified multiple rare and likely pathogenic variants in 19 genes co-segregating with disease through multiple generations.…”
Section: Towards a Molecular Stratification Of Sle—first Steps: The Rmentioning
confidence: 99%
“…Whole exome sequencing (WES) of SLE family trios has identified de novo mutations and potential novel SLE genes (Pullabhatla et al 2018 ). WES has also successfully identified rare variants that are likely pathogenic in SLE (Delgado-Vega et al 2018 ) and WGS of monozygotic twins discordant for SLE has found CNVs that may be associated with difference in SLE phenotype between twins (Chen et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%